Geminoid Studies Science and Technologies for Humanlike Teleoperated Androids - Ishiguro, Hiroshi; Dalla Libera, Fabio; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book describes the teleoperated android Geminoid, which has a very humanlike appearance, movements, and perceptions, requiring unique developmental techniques. The book facilitates understanding of the framework of android science and how to use it in real human societies. Creating body parts of soft material by molding an existing person using a shape-memory form provides not only the humanlike texture of the body surface but also safe physical interaction, that is, humanlike interpersonal interaction between people and the android. The teleoperation also highlights novel effects in telecommunication. Operators of the Geminoid feel the robot's body as their own, and people encountering the teleoperated Geminoid perceive the robot's body as being possessed by the operator as well. Where does the feeling of human presence come from? Can we transfer or reproduce human presence by technology? Geminoid may help to answer these questions. .
Development of an android system integrated with sensor networks -- Building artificial humans to understand humans -- Androids as a telecommunication medium with a humanlike presence -- Generating natural motion in an android by mapping human motion -- Evaluation of formant-based lip motion generation in teleoperated humanoid robots -- Analysis of head motions and speech, and head motion control in an android robot -- Generation of head motion during dialogue speech, and evaluation in humanoid robots -- Uncanny Valley of androids and the Lateral Inhibition Hypothesis -- Evaluation of robot appearance using a brain science technique -- Persistence of the Uncanny Valley -- Can a teleoperated android represent personal presence? - A case study with children -- Cues that trigger social transmission of disinhibition in young children -- Effects of observing eye contact between a robot and another person -- Can an android persuade you? -- Attitude change induced by different appearances of interactionagents -- Do robot appearance and speech affect people's attitude? Evaluation through the Ultimatum Game -- Isolation of physical traits and conversational content for personality design -- Body Ownership Transfer to a teleoperated android -- Effect of perspective change on Body Ownership Transfer -- Body Ownership Transfer by social interaction -- Exploring minimal requirement for Body Ownership Transfer by brain-computer interface -- Regulating emotion with Body Ownership Transfer -- Adjusting brain activity with Body Ownership Transfer -- At the café - Exploration and analysis of people's nonverbal behavior toward an android -- At the café - From an object to a subject -- At the hospital -- At the department store - can androids be a social entity in the real world? -- At the department store - can androids be salespeople in the real world? -- At the theater - Designing robot behavior in conversations based on contemporary colloquial theatre theory -- At the theater - Possibilities of androids aspoetry-reciting agents.
Keywords: Control engineering; Robotics; Automation; Multibody systems; Vibration; Mechanics, Applied; Artificial intelligence; Signal processing; User interfaces (Computer systems).; Human-computer interaction; Control, Robotics, Automation; Multibody Systems and Mechanical Vibrations; Artificial Intelligence; Signal, Speech and Image Processing; User Interfaces and Human Computer Interaction